Circular economy in the construction industry: A systematic literature review - Benachio, Gabriel Luiz Fritz; Freitas, Maria do Carmo Duarte; Tavares, Sergio Fernando (Journal of cleaner production, 2020)
The Construction Industry is responsible for over 30% of the extraction of natural resources, as well as 25% of solid waste generated in the world. This happens because the construction sector mostly adopts a linear economic model of “take, make, dispose”, using materials to the construction of buildings and disposing them at the end of life, since they are assembled for one time use and don’t retain potential for reuse. Over the last decades, a paradigm shift has been occurring in the industry at large, with the adoption of a Circular Economy model, that aims at keeping the materials in a closed loop to retain their maximum value, therefore with a greater potential of reducing the waste generation and resources extraction for the Construction Industry. This article aims at finding the recent developments of how Circular Economy can be used inside the construction industry. To achieve this goal, a systematic literature review was conducted, including 45 articles that were divided into six areas of research: development of Circular Economy, reuse of materials, material stocks, Circular Economy in the built environment, LCA analysis and material passport. An analysis of the content of these articles was made and the knowledge gaps in this area were identified, as well as table with known Circular Economy practices for the Construction Industry was created divided by life cycle stages. Finally, a discussion of each area of research and their findings is made. •Six different areas of research were found.•There is a lack of knowledge of standard practices of Circular Economy concepts inside the construction industry.•A list of known circular economy practices for the built environment was created.•Bigger focus should be given to economy models for Construction companies.•There is a potential to create a Community of Practice in the subject.